(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The current research aims to know efficiency levels of knowledge representation of information among Kirkuk university students and The statistically significant difference of the cognitive representation of information regarding gender(female ,males), specialization(scientific ,human ) and stage (first ,fourth). for the interactions between the cognitive efficiency variable of information and the variables (gender, specialization , stage). In order to achieve the objectives of the research ,the researcher adoption scale (The competency of the cognitive representation of the teacher)consisting of (46)paragraphs ,and each paragraph(5) within it (applies to me completely , applies to me often ,applies to me sometimes , applies to me rarely, never apples.